Evaluation the impact of saltwater intrution on Aquaculture in Shatt Al-Arab, Basra, Iraq - Al-Edany, B.T.; Ali, Malik H. (Iraqi Journal of Aquaculture, 2021)
The study made an evaluation to the effects of saltwater intrution in the Shatt Al-Arab river on the fish culture activites. Data reveals noticeable increase of investment in fresh water carp fish culture during the years 2009, 2010 and the next years. The documents of Basrah Agriculture Directerate indicated that 48 earthern ponds of an area nearly 3778 Acres were licensed and furthermore, nearly 380 floating fish cage farms were licensed about 26120 m2 area which represents the actual worked 1277 cages. However, the approved number of given licensed farms were 514 farms with at least 16 cages to each farm, which potentially can be invested a water area nearly 98688 m2, calculated to a cage of 4 x 3 x 2 (m2) dimentions. The total estimated production of earthern ponds was 3778–4723 t. annually, and that of floating cages farms was 3266–7800 t. annually. The total financial income of fish production in Basra proviance is estimated to be about 26133–35883 billion Iraqi dinar and more than 3000 persons were involved in the sector of fishculture and fisheries. The acute successive increases of salinity that Shatt Al-Arab river experienced, particularly during 2018 were caused large fish mortality and many fish farms were closed and have had very negative effects on the fish sector in Basrah proviance.